Pengaruh Pembelajaran 'Aqidah Dalam Pembentukan Karakter Siswa Kelas X Teknik Kendaraan Ringan (TKR) Smk Muhammadiyah Rembang Tahun Pelajaran 2016/2017 - Ratnasari, Paramitha Dwi, Drs. M. Darojat Ariyanto, M.Ag (2017)
The learning of 'aqidah (Islamic creed) is very influential to form a good character in the students because 'aqidah is a base for all Muslims in behaving in the daily life, by being based on al-Qur'ān and as-Sunah. So is the character, character is a good personality that must be owned by every person. One of ways to form character in SMK Muhammadiyah Rembang is through the learning of 'aqidah, therefore, it can shape the students to be accustomed to something they did not get in their home and their environment such as being accustomed to pray on time and to pray in congregation, to recite al-Qur'ān, to be honest, to be disciplined, to preserve the environment, etc. Meanwhile, the problem statements in this research are: how is the influence of the learning of 'aqidah in forming the character of the 10th grade of TKR. What is the motivator in forming the character the 10th grade of TKR through the learning of 'aqidah. And whatare obstacles faced in forming the character through the learning of 'aqidah held in SMK Muhammadiyah Rembang. In this research, the objects are the students of the 10th grade of TKR. Type of the research is a field research by using a quantitative approach. The method of data collection used questionnaire, interview, observation, documentation, and data analysis. The purposes of this research are to know the influence of the learning of 'aqidah in forming the character, to know the supporting factors in forming the character, and to know the obstacles faced in forming the character in the 10th grade of TKR of SMK Muhammadiyah Rembang. From the results of the research, in can be concluded that there is a strong influence of the learning of 'aqidah in forming the character of the 10th grade of TKR in SMK Muhammadiyah Rembang with the supporting factors and the in hibiting factors faced. From the test result of significant conjectures while the hypothesisis know Ha (Alternative Hypothesis) that the influence of learning 'aqidah in forming the character the students of the 10th grade of TKR SMK Muhammadiyah Rembang received, and Ho (Null hypothesis) there is no influence of learning 'aqidah in forming the character the student of the 10th grade of TKR SMK Muhammadiyah Rembang rejected. By forming the students' character, it can create graduates who are able to face the challenges outside by having a good character with a life guidance based on Islamic sharia.